Core-genome guided novel therapeutic targets identification and chimeric vaccine designing against Rickettsia rickettsii - Fizza Arshad; Asifa Sarfraz; Muhammad Shehroz; Umar Nishan; Asia Perveen; Riaz Ullah; Mohamed A. Ibrahim; Mohibullah Shah (Scientific Reports)
Abstract Rocky Mountain Spotted Fever, caused by the gram-negative intracellular bacteria Rickettsia rickettsii, is a serious tick-borne infection with a fatality rate of 20–30%, if not treated. Since it is the most serious rickettsial disease in North America, modified prevention and treatment strategies are of critical importance. In order to find new therapeutic targets and create multiepitope vaccines, this study integrated subtractive proteomics with reverse vaccinology. The core genome of R. rickettsii was investigated, resulting in the identification of seven essential, human non-homologous proteins as potential drug targets, as well as four antigenic, non-allergenic proteins suitable for vaccine development. Using conserved antigenic peptides, two chimeric vaccine constructs were developed and assessed using molecular docking, molecular dynamics simulations, principal component analysis, MM-GBSA binding free energy, and dynamic cross-correlation matrix studies. The high immunogenic potential was indicated by the vaccine designs’ robust and consistent interactions with human immunological receptors. Their capacity to trigger strong humoral and cellular immunological responses was further demonstrated by in silico immune simulations. The persistent interactions of vaccine V1 and V2 with human immunological receptor demonstrated that these might have high immunogenic potential. Moreover, the identified drug targets were annotated for essential biological processes, which shed light on their therapeutic potential. The vaccine constructs were cloned and expressed in suitable systems. This study displays a comprehensive strategy for managing Rocky Mountain Spotted Fever via rational vaccine development. Further experimental research is needed to confirm the immunogenicity of the vaccines and the druggability of identified targets, establishing the path toward effective RMSF management.